Peluang Dan Ancaman Perdagangan Internasional Biji Kakao Studi Kasus: Indonesia Dengan Malaysia - Lubna Salsabila; Wini Yuliani; Laditry Susthia Syariefa; Muhammad Dio Saputra; Daspar (Jurnal Ekonomi dan Bisnis Digital, 2024)
Indonesia ranks third as the largest cocoa producer globally. The majority of its cocoa output is marketed and exported. Hence, the government implements regulations to restrict exports. Reduced cocoa exports result in decreased cocoa production. Indonesia's agricultural sector holds significant sway in the national economy as it can deliver superior products for global market entry. While cocoa also contributes to the development of the agricultural industry region. The most important product of this sector in Indonesia is cocoa. Hence, it's crucial to assess both the prospects and challenges within the cocoa industry. International trade plays a pivotal role in enhancing a nation's economic standing. This research aims to analyze opportunities and threats in international trade in cocoa beans between Indonesia and Malaysia. By using a relevant theoretical framework, this research provides in-depth insight into the dynamics of cocoa bean trade between the two countries.The export value of cocoa beans, being a raw material, significantly impacts overall exports, as inadequate processing does not enhance the product's value. In the context of competition, Indonesian cocoa beans are exported to international markets, and Malaysia as the main destination has a comparative advantage thanks to relatively cheaper prices, so that Indonesia can compete in this market.